PENANAMAN NILAI-MORAL PADA ANAK DALAM KELUARGA NELAYAN DUKUH TANJUNGSARI - Permana, Irfan Sidik; Munandar, M Aris (Unnes Civic Education Journal, 2015)
This article aims at examining the implementation of vocational skills education in school. The location of the research is in SMA PGRI 3 Tayu. Issues examined in this article include kinds of vocational skill developed, how the school teaches vocational skills training, what the barriers and pushing factors are in the implementation of life skill. This study uses a descriptive qualitative research methods. The results showed that the implementation of vocational skills training in high skill PGRI 3 Tayu going well because of good cooperation from various parties. Skills taught vocational skills such as skills growing papaya, dragon fruit, orchids, flower soft-shelled, mangroves, making organic fertilizer, salted eggs, duck eggs incubator tool making, automotive, beauty, planting flowers antorium, raising chickens, raising catfish, marching band, and scouts. The factor that contributes to the success is is the availability of facilities and infrastructure, funding, teacher or teachers, the support of the parents themselves, the support of the government and the support of the business community. The inhibiting factor is the lack of land available for the implementation of these skills and the tendency of the students to become a civil servant and employees in bona fide companies.